2022
DOI: 10.1007/s00382-022-06174-8
|View full text |Cite
|
Sign up to set email alerts
|

Association between regional summer monsoon onset in South Asia and Tibetan Plateau thermal forcing

Abstract: By using multiple data sources and numerical simulation results from the atmospheric general circulation model (AGCM) of CAM4.0 (Community Atmosphere Model, version 4), we investigated the effect of thermal forcing over the Tibetan Plateau (TP) on the onset of the summer monsoon in the Arabian Sea (AS) and India. Results indicate that the spatial distribution of diabatic heating over the TP in May is a southeastern–northwestern inverse pattern. This diabatic heating shows a robust negative relationship with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 77 publications
(123 reference statements)
0
7
0
Order By: Relevance
“…Because there is no diabatic heating at different pressure levels in ERA5, we used MERRA‐2 diabatic heating at a resolution of 0.625° × 0.5° ranging from 1000 to 200 hPa (Gelaro et al., 2017). The used MERRA‐2 diabatic heating over the TP has also been compared with the Japanese 55‐yr Reanalysis (JRA‐55) data (D. Hu et al., 2022; Kobayashi et al., 2015), and they show significantly high consistency in terms of interannual variations (Figure S2 in the Supporting Information ). An improved topography is used in the MERRA‐2 model and can better capture the topography variations at different pressure levels over the TP (figures not shown).…”
Section: Methodsmentioning
confidence: 99%
“…Because there is no diabatic heating at different pressure levels in ERA5, we used MERRA‐2 diabatic heating at a resolution of 0.625° × 0.5° ranging from 1000 to 200 hPa (Gelaro et al., 2017). The used MERRA‐2 diabatic heating over the TP has also been compared with the Japanese 55‐yr Reanalysis (JRA‐55) data (D. Hu et al., 2022; Kobayashi et al., 2015), and they show significantly high consistency in terms of interannual variations (Figure S2 in the Supporting Information ). An improved topography is used in the MERRA‐2 model and can better capture the topography variations at different pressure levels over the TP (figures not shown).…”
Section: Methodsmentioning
confidence: 99%
“…The dynamic and thermodynamic effects of the Qinghai-Tibet Plateau (QTP) on regional and global weather and climate have been widely recognized (Wu et al 2007;Wu et al 1997;Duan et al 2013;He et al 2015). Numerous studies have shown that the strength of atmospheric heat source over the QTP not only affects the strength of the East Asian Summer Monsoon, but also plays an important role in its outbreak, evolution, and promotion (Wu et al 2015;Xiao et al 2016;Wang et al 2017;Hu et al 2022;Yu et al 2023). The QTP is also important in the strength and spatial pattern of summer precipitation in eastern China through its thermodynamic effect (Xu et al 2013;Lai and Gong 2017;Shi et al 2019;Huang et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Together, they induce the monsoon onset over India by extending the South Asian High westward (B. Liu et al., 2013; Wu & Liu, 2014; Y. Zhang et al., 2014). At the interannual timescale, some studies have proposed a positive correlation of the BOB monsoon onset time with those of the SCS and India after the 1980s (Hu et al., 2022; Tamura & Koike, 2010; Zeng et al., 2021). However, since the criteria employed for ASM onset differ across studies, the interannual relationship between each stage of ASMOP remains uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…However, since the criteria employed for ASM onset differ across studies, the interannual relationship between each stage of ASMOP remains uncertain. Furthermore, the interannual variability of the dates of ASM onset relies on the ENSO‐related sea surface temperature anomalies (SSTAs) (Ju & Slingo, 1995; X. Wang et al., 2013; Webster & Yang, 1992), thermal forcing of the Tibetan Plateau (Hu et al., 2022; Li & Yanai, 1996; B. Liu & Zhu, 2021), and land surface temperature over the Eurasian continent (Choudhury et al., 2019; Zhu & Li, 2017). However, it remains unclear as to how these factors, especially the extra‐equatorial SSTAs, affect the interannual changes in the stepwise ASMOP.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation